Why Are Native Hawaiians Underrepresented in Hawai‘i's Older Adult Population? Exploring Social and Behavioral Factors of Longevity - Lana Sue Ka‘opua; Kathryn L. Braun; Colette V. Browne; Noreen Mokuau; Chai-Bin Park (Journal of Aging Research)
Native Hawaiians comprise 24.3% of Hawai‘i's population, but only 12.6% of the state's older adults. Few published studies have compared health indicators across ethnicities for the state's older adult population or focused on disparities of Native Hawaiian elders. The current study examines data from two state surveillance programs, with attention to cause of death and social-behavioral factors relevant to elders. Findings reveal that Native Hawaiians have the largest years of productive life lost and the lowest life expectancy, when compared to the state's other major ethnic groups. Heart disease and cancer are leading causes of premature mortality. Native Hawaiian elders are more likely to report behavioral health risks such as smoking and obesity, live within/below 100–199% of the poverty level, and find cost a barrier to seeking care. Indicated is the need for affordable care across the lifespan and health services continuum. Future research might explain behavioral factors as influenced by social determinants, including historical trauma on Native Hawaiian longevity.